ASSESSING SHS STUDENTS’ NEEDS E-WORKSHEET BASED ON DIFFERENTIATED INSTRUCTION - Pratama, Miftahunajah Aditiya; Sofendi, Sofendi; Vianty, Machdalena (English Review: Journal of English Education, 2024)
Education in Indonesia has developed a lot over time. Differentiated learning in the independent curriculum allows teachers to adjust instruction to meet the diverse needs of students. This approach acknowledges that students have varied learning styles, strengths, and interests. This study aimed to uncover the needs of senior high school students for developing differentiated instruction-based e-worksheet in English subjects for 10th Grade students. This study was conducted at MAN 3 Palembang to explore the perspectives of 30 tenth-grade students and their English teacher. To achieve the objectives of this study, a mixed-methods approach was applied, combining both quantitative and qualitative data collection methods. The data were obtained using a questionnaire and semi-structured interviews. Participants of this study were the tenth-grade students and English teacher. The result of the needs analysis showed that: 1) English learning materials with technology integration are limited and need development. 2) Students need differentiated instruction-based e-worksheets for reading that match their abilities. Therefore, this study is also used as the preliminary study to develop a differentiated instruction-based e-worksheet that can be used for English learning.